Electrifying Organic Synthesis. Issue 20 (7th March 2018) - Wiebe, Anton; Gieshoff, Tile; Möhle, Sabine; Rodrigo, Eduardo; Zirbes, Michael; Waldvogel, Siegfried R.
Abstract: The direct synthetic organic use of electricity is currently experiencing a renaissance. More synthetically oriented laboratories working in this area are exploiting both novel and more traditional concepts, paving the way to broader applications of this niche technology. As only electrons serve as reagents, the generation of reagent waste is efficiently avoided. Moreover, stoichiometric reagents can be regenerated and allow a transformation to be conducted in an electrocatalytic fashion. However, the application of electroorganic transformations is more than minimizing the waste footprint, it rather gives rise to inherently safe processes, reduces the number of steps of many syntheses, allows for milder reaction conditions, provides alternative means to access desired structural entities, and creates intellectual property (IP) space. When the electricity originates from renewable resources, this surplus might be directly employed as a terminal oxidizing or reducing agent, providing an ultra‐sustainable and therefore highly attractive technique. This Review surveys recent developments in electrochemical synthesis that will influence the future of this area. Abstract : Electrons serve as the only reagent in electroorganic transformations, avoiding the generation of reagent waste. However, the application of electroorganic transformations is more than minimizing the waste footprint, it rather gives rise to inherently safe processes and milder transformations, reduces the number of steps of many syntheses, and provides alternative methods to access desired structural entities.